Perspektif Gender Remaja Awal dalam Kecerdasan Emosional - Fititianingsih, Roro Ambar; Sukmawardani, Chandra Dewi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Adolescence is a phase where a person experiences emotional changes in forming a more mature and independent person. This research explores the differences and similarities between the two objects studied. The research method uses quantitative methods with a comparative description model. The research population was 168 people. The research sample was a total sample of 120 people. The results of processing the research data using the difference test analysis formula (T-Test) showed that the t-test value with calculated t was -0.993 with a significance of 0.323. Therefore, the importance of 0.323>0.05 shows that the emotional intelligence of female and male students is in the same category: medium. So, it can be concluded that there is no difference between the emotional intelligence of female and male students at Wijaya Kusuma High School, East Jakarta.